The Effectiveness of Home Visiting Programs for Preventing Child Maltreatment - Apóstolo, Jorge Manuel Amado (2017)
Abstract Summary: We should have nterventions in a way to fight child abuse or neglect. Could home visiting programms help our families? What kind of results have we? Are the programms effective? What is the nurse role? Are the nurses in a good position? Learning Activity: LEARNING OBJECTIVES EXPANDED CONTENT OUTLINE The learner will be able to identify and discuss the importance and implications of evidence about home visiting programs in preventing child abuse and neglect. 1. Introduction. The situation of abuse and neglect child in our societies. Effective programms or interventions. The learner will be able to recognize and discuss some outcomes, using the home visiting programs in prevention of maltreatment children. 2.The Research design. 3.Results 4.Conclusions and implications Abstract Text: Purpose: Child abuse or neglect and violence against children and young people are a structural problem in all societies even in, considered, developed societies. "Child maltreatment is a great public health concern that has long-term mental and physical health consequences and can result in death" (Mejdoubi, van den Heijkant, van Leerdam, Crijnen & Hirasing, 2015, p. 1). So, the consequences of abuse or neglect situations and violence in general, in future are potentially negative and put the children in a difficult condition. Usually, these kind of problems, are associated with several environmental and family conditions that sometimes act as a trigger in a bad circumstance, or as protective key. We need effective programs that could avoid the problems and protect children and young people, in a way to an excellent development. Actually, home visit programs are interventions that foster close and reliable relationships among health professionals, families, and the community. Evidence from three United States randomized controlled trials (RCTs) on the effectiveness of this intervention at improving pregnancy outcomes, improving child health and development, and increasing maternal economic selfsufficiency is robust (Jack, Catherine, Gonzalez, MacMillan, Sheehan, & Waddlel, 2015) but we need more evidence about the positive impact of these programs, especially on at-risk families. In this context, the main objective of the research was to identify evidence of effectiveness of the home visiting programs in the prevention or recurrence of maltreatment of children and young people. Methods: We proceed to an integrative review of the literature. With the search expression Child * AND Neglect * OR Abuse* AND Home visiting program * AND Effect *. We have chosen the online databases: Medline; Cinahl; MedicLatina; Academic Search Complete. Through the PICO strategy, we have defined criteria for inclusion and exclusion of articles. We included: Participants - pregnant and parents of children up to five years of age. Interventions - the home visit. Comparisons - among participants who received home visits and participants who received usual care. Outcomes - indicators of effectiveness of home visiting programs. Results: We identified as indicators of the effectiveness of home visiting programs: • Increased prenatal care • Weight gain at birth • Reducing preterm deliveries • Increased use of health services (child health, family planning, vaccination) and community social services • Improving Pregnancy Nutrition • Reduction of smoking habits • Increase in spacing between pregnancies • Increase in parental employment • Reduction in the demand for emergencies • Reduction of accidents and poisoning • Reduction of corporal punishment practices and appropriate use of discipline in children • Reduction of intra-family gender violence • Improving children's growth and development • Reduction of criminal conduct of parents • Reduction in demand for social aid • Reducing drug and alcohol abuse in the mother • In the short term, there is a significant reduction in the number of physical assaults and neglect in the recurrence of maltreatment. • More effective in preventing abusive behavior than in correcting it. • Higher prevalence of positive parental behaviors, more development of family affective bond and greater parental qualifications. • Greater potential for adjustment and use of coping strategies in generically stressful situations. These include the significantly more positive effects in families with socioeconomic problems and parents with preterm infants. • Early identification of vulnerable situations, potential violence, especially if implemented in the prenatal period. • As regards the recurrence of maltreatment, a significant reduction in the number of physical assaults and neglect is evident in the short term. • Effectiveness is higher in young and primiparous mothers when compared to multiparous mothers, because their behavior may become more flexible, plastic and adjusted. Conclusion: These programs seem to particularly benefit families with comparative disadvantages, situations of socioeconomic risk, and diverse vulnerabilities, and the effectiveness is greatest in young and primiparous mothers. The higher prevalence of adjusted parental behaviors, adherence to positive parenting, greater expression of family affective bonds, and greater demonstration of parental empowerment may help to protect children in difficult contexts. This greater potential of adaptation and recourse to coping strategies in situations that potentiate individual and family stress, such as families with socioeconomic life events and parents with premature babies. However, there are doubts about the cost-benefit of some programs, requiring the design to be sufficiently tailored, taking into account the differences in context, culture, values, beliefs, and range of interfering factors in the functioning of each family. References: Mejdoubi, J., van den Heijkant, S. C. C. M., van Leerdam, F J. M., Heymans, M. W., Crijnen, A. & Hirasing, R. A. (2015). The Effect of VoorZorg, the Dutch Nurse-Family Partnership, on Child Maltreatment and Development: A Randomized Controlled Trial. PLOS ONE. DOI:10.1371/journal.pone.0120182, 1-14. Jack, S.M., Catherine, N., Gonzalez, A., MacMillan, H.L., Sheehan, D. & Waddlel, D. , (2015). Adapting, piloting and evaluating complex public health interventions: lessons learned from the Nurse-Family Partnership in Canadian public health settings. Health Promot Chronic Dis Prev Can. Vol. 35 (8-9). 151-9.